Incidence of contraindications to immunisation. Issue 7 (July 1989) - Hewitt, M
Abstract : A cohort of 522 children entering primary school were reviewed for contraindications to immunisation. Every child in the group would have been eligible to receive diphtheria, tetanus, polio, and measles immunisation if the current (1988) Department of Health and Social Security (DHSS) guidelines had been followed. Only 2.5% of the cohort met the DHSS contraindications to pertussis immunisation.